Character Education Application in Thematic-Integrative Learning of Curriculum 2013 - Hani Dwi Hastuti; Marsigit Marsigit (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2020)
This research development aims to produce thematic-integrative teaching materials based on a scientific approach. The product produced aims to develop a confident character. Teaching materials developed get positive responses from students with excellent task completion achievement, amounting to 81.5%. This is evidenced based on the results of expert assessments which show that teaching material developed from the aspect of content eligibility is categorized as "very good" with an average of 64.5, aspects of language are categorized as "good" with an average of 31, aspects of presenting the category of "very good" with an average of 59, and the aspect of graphics categorized as "very good" with an average of 55. Thematic-integrative teaching materials based on a scientific approach with the theme "Beautiful Togetherness" to develop self-confidence and improve learning outcomes of grade IV elementary school students in learning.